The impact of heterogeneous salt velocity models on the gross rock volume estimation: an example from the Santos Basin pre-salt, Brazil. Issue 4 (2021) - Maul, Alexandre; Cetale, Marco; Guizan, Cleverson; Corbett, Patrick; Underhill, John R.; Teixeira, Leonardo; Pontes, Rodrigo; González, María
No abstract available